Social Competencies of Students of Science and Social Majors for Volunteer Work - Anna Kanios; Anna Weissbrot-Koziarska (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
The article discusses the recognition of social competencies of students of science and social majors to do voluntary work. The theoretical concept on which the research is based is the concept of social competencies by J. Skrzypczak, who sees them as “the ability to do something, depending on the familiarity of knowledge, skills and abilities included in it, as well as on the degree of conviction about the need of using that ability.” The main purpose of the research is to diagnose the social competencies of students of science and social majors to do voluntary work and to identify the differences between groups in this respect. The method of diagnostic survey was chosen for the purposes of the study. Research has shown slight differences between the students of science and social majors. They only concern the assessment of one's own level of motivation to help.